2019
DOI: 10.1002/alr.22413
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray analysis reveals that cofilin expression is a poor prognostic factor in juvenile nasopharyngeal angiofibroma

Abstract: Background: Juvenile nasopharyngeal angiofibroma (JNA) has a high recurrence rate a er surgery. Cofilin overexpression is associated with increased tumor cell metastasis, and progression of various human cancers. However, studies on cofilin expression in JNA are rare. The purpose of this study was to investigate the expression and localization of cofilin in a tissue microarray (TMA) of JNA specimens. In addition, we also analyzed its correlation with clinicopathological features and recurrence. Methods:Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similarly, juvenile nasopharyngeal angiofibroma (JNA) may recur after surgery. In this regard, Li et al . indicated that cofilin was an independent prognostic marker for JNA recurrence and might be a novel therapeutic target for extensive JNA.…”
mentioning
confidence: 99%
“…Similarly, juvenile nasopharyngeal angiofibroma (JNA) may recur after surgery. In this regard, Li et al . indicated that cofilin was an independent prognostic marker for JNA recurrence and might be a novel therapeutic target for extensive JNA.…”
mentioning
confidence: 99%